Nomes gerais e outras formas de indeterminação do sujeito no portuguêsoral de Bambuí-MG - Fernanda Carla de Oliveira (2018)
The forms of indetermination of the subject have been researched by several authors, such as Milanez (1982), Menon (1994), Setti (1997), Godoy (1999), Carvalho (2010), Souza (2014), among others. All of them have concluded that there are many other ways to indeterminatethan the forms proposed by traditional grammars. In this regard, considering the variationist sociolinguistics perspective, this study aims to observe the relevance of general nouns in the set of indeterminate variables. General nouns are defined by Halliday and Hasan (1995 [1976]) as a borderline case between a lexical item and a grammatical item since they contain minimal semantic features, and they were selected for this study because some researches have already shown that these items are capable of indeterminacy. The data analyzedcomprises sociolinguistic recordings gathered in the city of Bambuí, located in the central west of Minas Gerais. The general nouns found in the corpus were pessoa, pessoal, pessoas, cara, homem, povo, fulano and ser humano. The other forms studied refer to those that havealready been discussed in previous researches, that is, a gente, você/ocê/cê, nós/nóis, eles/ês, verb in third person singular without explicit subject (Ø + V3PS), verb in third person plural without explicit subject (Ø + V3PP), verb in infinitive without explicit subject (Ø + VINF) andse. The extralinguistic factors analyzed are sex, schooling, and age, and the linguistic factors studied are presence or absence of locative, verbal tense, mood, presence or absence of anaphora, degree of indeterminacy, type of clause and more or less collective. The programused for the data analysis is GoldVarb X. In relation to the results, it was found that the general nouns occupy the third position in the set of variables, preceded only by the forms a gente and você. Furthermore, povo was the most recurrent general noun in the corpus. Womenslightly favored, with regard to linguistic factors, the general nouns that present absence of anaphora, total indetermination, imperfect tense, and simple sentence.